'Play it Again, Sam' – intertextuality, authorship and expectations in The Bloody Olive. Issue 1 (1st April 2014) - Shaw, Nathan
Whether early literary adaptations or postmodern, pop culture stuffed millennium movies, cinema has continually showcased its penchant for intertextuality. Simultaneously, genre films have constructed a network of paradigms allowing discerning audiences to expect the previously unexpected. These interconnecting elements are prevalent, and toyed with, throughout short film noir pastiche The Bloody Olive.